The Effectiveness of Emotional Freedom Techniques (EFT) on The Childbirth Anxiety in Primigravida in The Third Trimester of Pregnancy - Maria Magdalena Saragi R; Marganda H. Limbong (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Pregnant primigravida women generally experience fear, anxiety, and worry during pregnancy and while facing childbirth and the postpartum period. Anxiety has been identified as a contributing factor in prolonged labour and fetal death. Stress and anxiety management strategies can be implemented using psychotherapy methods such as emotional freedom techniques which is fundamental principle of EFT is to activate and cessation wave through the stimulation of meridian spot to brain, usually tapping. This study employs a quasi-experimental methodology. The research method employed is a single-group pretest-posttest design, which lacks a standard group. This design demands measuring anxiety levels with a pretest conducted before the Emotional Freedom Techniques (EFT) intervention and a posttest conducted afterward. The population under investigation comprises all pregnant primigravida in Tapanuli Tengah Regency between April and August 2024. A purposive sampling technique was employed to obtain third-trimester primigravida without complications as respondents. A total of 30 respondents met the inclusion criteria. The research objectiove is to ascertain the levels of anxiety before and after the application of Emotional Freedom Techniques on pregnant primigravida women and to understand how the following works of EFT on their anxiety during childbirth. SPSS 25 is a helping tool to analyse the effect using a paired t-test. The results indicate that there is an effect of Emotional Freedom Techniques in lowering an uneasiness in pregnant primigravida women in their third term during childbirth, with a mean of 20.067 and a p-value of 0.000 < (α = 0.05). Based on the research, it can be concluded that Emotional Freedom Techniques has an effect in lowering an uneasiness in pregnant primigravida women in their third term during childbirth. Keywords: Anxiety, Emotional Freedom Technique, Primigravida Pregnant Woman